Dual task and postural control in Alzheimer's and Parkinson's disease - Larissa Pires de Andrade; Natália Madalena Rinaldi; Flávia Gomes de Melo Coelho; Kátia Tanaka; Florindo Stella; Lilian Teresa Bucken Gobbi (Universidade Estadual Paulista (UNESP), 2014)
Patients with neurodegenerative diseases are required to use cognitive resources while maintaining postural control. The aim of this study was to investigate the effects of a frontal cognitive task on postural control in patients with Alzheimer, Parkinson and controls. Thirty-eight participants were instructed to stand upright on a force platform in two experimental conditions: single and dual task. Participants with Parkinson's disease presented an increase in the coefficient of variation greater than 100% in the dual task as compared to the single task for center of pressure (COP) area and COP path. In addition, patients with Parkinson's and Alzheimer's disease had a higher number of errors during the execution of the cognitive task when compared to the group of elderly without neurodegenerative diseases. The motor cortex, which is engaged in postural control, does not seem to compete with frontal brain regions in the performance of the cognitive task. However, patients with Parkinson's and Alzheimer's disease presented worsened performance in cognitive task.